A STUDY ON THE POLITICAL ECONOMIC EPISTEMOLOGY OF HIZBUT TAHRIR INDONESIA (HTI) - Irkhami, Nafis (IAIN Tulungagung, 2018)
A correct understanding of the fundamental elements in Islamic political economy becomes a necessity for its development. This paper attempts to trace the conceptual understanding of Hizbut Tahrir Indonesia (HTI) regarding the basic elements of science which includes worldview and epistemology. Its position in constructing Islamic political-economic methodology is also a major topic. There are differences in the vision, epistemology, and framework of Islamic political-economic methodology from those of the West. These differences lead to the differences in scientific development. At the level of praxis, it also creates differences in policy determination. Meanwhile, logic, coherence, and consistency are important prerequisites for the scientific approach. Islamic political economics must be studied with our own worldview and epistemology. However, hand, we cannot deny the role and position of political and economic science in the process of developing an Islamic political economy. The study ofHTI’s political-economic epistemology covers the intervention and role of the state in the economy, especially in terms of public policy.